Analisis Karakter Pada Tokoh Utama Dalam Satua Ni Diah Tantri Serta Implikasinya Terhadap Perempuan Hindu Masa Kini - Ni Putu Eka Juliantini; I Ketut Sudarsana (Kamaya: Jurnal Ilmu Agama, 2018)
One of the most familiar literary works in Balinese society is the traditional Bali prose in the form of folklore. Among the many folklore in Bali, folklore Ni Diah Tantri by I Made Pasek selected in this research because have advantages that lies in story line which give many useful advice in main life in modern era like today. The phenomenon of the behavior of the society of late is better known as moral degradation. The diminishing of the main values in society including the value of the characters caused by the Indonesian people do not like to read books, on of which is reading the literary works. The existence of folklore Ni Diah Tantri already familiar in the main community of young generation of Bali is expected to become a medium of learning as a good character builder.